Paris, Japan, and modernity: a vexed ratio - Chang, Ting (Ashgate Publishing, 2015)
This essay uses mobility as a way to tackle the nominal question, “Is Paris Still the Capital of the Nineteenth Century?” By examining the illustrated travel narratives of two Frenchmen in Japan, Émile Guimet, founder of the eponymous museum of Asian art in Paris, and the artist Félix Régamey, who accompanied him on his tour in 1876, I argue that travel and transport provide a vehicle through which to challenge the centrality of Paris, and by extension, the West in the nineteenth century. By moving our attention to Japan, we can better understand the changing balance of power between East and West in the nineteenth century, and the contested terms of center and periphery that have preoccupied recent scholars in the humanities and social sciences.